Cardiorespiratory fitness in patients with rheumatoid arthritis is associated with the patient global assessment but not with objective measurements of disease activity - Mari Hoff; Ranjeny Thomas; Marthe Halsan Liff; Thomas Fremo; Ulrik Wisløff; Vibeke Videm (RMD Open, 2019)
Objective Patients with rheumatoid arthritis (RA) suffer from more cardiovascular disease (CVD), and develop cardiovascular risk factors at an earlier age than the general population. Cardiorespiratory fitness (CRF) is an important predictor of cardiovascular health. There are few data regarding CRF of RA patients, measured as peak oxygen uptake (VO2peak) by the gold standard method; cardiopulmonary exercise testing. We compared CRF in RA patients to those from a healthy population, and investigated if risk factors for CVD and RA-specific variables including subjective and objective disease activity measures were associated with CRF in RA patients.Methods VO2peak tests of RA patients (n=93) were compared to those of an age-matched and gender-matched healthy population (n=4631) from the Nord-Trøndelag Health Study. Predictors of VO2peak were found using Lasso (least absolute shrinkage and selection operator) regression, followed by standardised multiple linear regression.Results Women with RA ≥40 years and men with RA aged 40–49 years or 60–69 years had up to 20% lower CRF than the healthy population in the same age groups. By relative importance, body mass index (standardised coefficient=−0.25, p<0.001), physical activity level (coefficient=0.21, p<0.001), patient global assessment (PGA; coefficient=−0.14, p=0.006), systolic blood pressure (coefficient=−0.12, p=0.016), resting heart rate (coefficient=−0.11, p=0.032) and smoking (coefficient=−0.10, p=0.046) were significant predictors of CRF (R2=0.82, gender-adjusted and age-adjusted).Conclusion CRF in RA patients was lower than in a healthy population. CRF was associated with common risk factors for CVD and the PGA score. Focusing on fitness in RA patients may improve cardiovascular health.